Genetic diversity of tuba plants, and toxicity of their rotenoids formulated as nano-emulsion against Plutella xylostella L - Asib, Norhayu (2015)
Rotenone found in the crude extract from the roots of Tuba plants is commonly used as a bioinsecticide to control insect pests of horticultural crops. The control obtained on insect pests varies greatly and this could probably be due to the source and process of extraction, toxicant preparation and application in the field. The need to improve the quality of the rotenone as botanical insecticide and to obtain consistent control of insect pest led to the studies with following objectives; 1) to identify the diversity of Tubaplants based on Random Amplified Polymorphic DNA (RAPD) analysis, Internal Transcribe Spacer (ITS) marker and their morphological characteristics, 2) to extract,and characterize bioactive compound rotenone from Tuba plants, 3) to prepare the biobased emulsion formulation of rotenone extract and 4) to evaluate the insecticidal properties of the emulsion formulation of rotenone against Diamondback moth (DBM). Nine accession were collected from Peninsular Malaysia and subjected for identification by the Random Amplified Polymorphic DNA. The presence and absence of amplified allele was analysed using NTSYS to obtain dendrogram and coefficient of similarity index. The results obtained on the number of polymorphics loci, the percentage of polymorphics loci, Shannon’s Information index and the effective number of alleles were 318, 98.45%, 0.4571 and 1.4533 respectively indicating the diversity of accessions studied. ITS sequences were used to identify the species in which double stranded DNA of the ITS region from nine accessions was amplified with the universal primer pairs ITS 4 and ITS 5. The mean number substitution per site and the number of nucleotides changes obtained for each accession plants indicated that there were 4 different species within the accessions. Basedon , morphological data of leaves examined analyzed using multivariate analysis to obtain the Principal components, dendrogram and coefficient of similarity index showed that all accessions could be clearly separated from each other based on leaf radians technique even though most of them have very similar shape.The rotenone from nine Tuba accessions was extracted using acetone. The extracts were then quantified using the High Performance Liquid Chromatography with Photodiode Array detector against the analytical standard of rotenone. All accessions contained rotenone with the concentration varies from 40 to 1500 μg/mL. The chemical elucidation of rotenone from nine accessions was conducted using Liquid Chromatography Mass Spectrometer. Rotenone and deguelin were found from the elucidation of each accession at retention time of 5.7 and 6.6 minute, respectively. Both have similar mass of 395.1489 with the empirical formula of C23H21O6. Three accessions i.e. Paraderris lianoides KJ579433 (Tuba Tualang) from Tasik Bera, Pahang, Derris elliptica KJ579428 (Tuba Derris) from Universiti Putra Malaysia and D. elliptica KJ579429 (Tuba Merah) from Jerangau, Terengganu were chosen based on the highest concentration (> 1%) of rotenone obtained for the preparation of emulsion formulation. The emulsion system was developed for formulating the extract by constructing ternary phase diagrams with 70% (w/w) emulsion system constituted of non-ionic surfactant(s), carrier and water, and 30% (w/w) rotenone extract as active ingredient. A total of thirteen formulations comprising four of Tuba Merah (F1TM7B, F2TM14B, F3TM21B and F4TM14B), five of Tuba Tualang (F5TT7B, F6TT14B, F7TT21B, F8TT21S and F9TT14S) and four of Tuba Derris (F10TD7S, F11TD21Sil, F12TD7Sil and F13TD7Sil) were made. All formulations showed particle size of less than 100nm and surface tension value of below 30 mN/m. All formulations were also stable at 25°C for two months, the agglomeration was observed for all formulations and stable at temperature 54°C except for formulation F13TD7Sil.The toxicity of rotenone was obtained from nine Tuba accessions evaluated through dose mortality and antifeedant bioassays against DBM. The leaf-dip technique was used to obtain dose-mortality response of rotenone in the nano-emulsion formulations. All rotenone formulations gave 100% mortality 72 hours after treatment at concentration of 273 μg/mL. The F7TT21B formulation gave the lowest LC50 value of 0.02 μg/mL while F1TM7B, F5TT7B, F6TT14B and F4TM14B gave LC50 value of 10.016, 10.298, 6.741 and 5.044 μg/mL, respectively indicating influence of formulation on the toxicity of rotenone. Surfactant mixture of Agnique MBL 510H and Agnique MBL 530B,and carrier dimethylamide (Agnique AMD810) in the formulations played important role in increasing the mortality. In the antifeedant study, the formulation with mixed surfactant differed significantly in Feeding Deterrence Index compared with the control.Dietary utilization by the DBM was severely affected when fed on mustard leaves treated with all formulations of rotenone. The F6TT14B showed significantly lower consumption intake (0.07 mg/mg/day) compared to other formulations. The relative consumption rate was significantly reduced for F1TM7B, F3TM21B, F6TT14B, F9TT14S, F11TD21Sil and F12TD7Sil compared with the other formulations and control.The F6TT14B showed the lowest RGR compared to the other formulations (0.25 mg/mg/day). The percentage of efficiency of conversion of ingested food of F8TT21S (27.81%) and F9TT14S (28.53%) was significantly better compared to the control (55.42%) and other formulations. The efficiency of conversion of digested (ECD) showed that all the formulations differed significantly compared with the control. The ECD values of F2TM14B, F3TM21B, F4TM14B, F7TT21B, F11TD21Sil, F12TD7Sil and F13TD7Sil ranged from 3.95% to 5.37% and differed significantly compared with the control. The reduction in dietary utilization that reduced the growth may result from both behavioural and physiological (post-ingestive) effects.